Using corrugation stitch in submammary fold at the reconstructive breast surgery - N. V. Zelenin; N. E. Manturova; V. N. Zelenin; I. A. Shurygina (Acta Biomedica Scientifica, 2016)
The aim of the research was to develop a new technique for suturing the surgical incision in submammary area after subpectoral reconstructive breast surgery with good cosmetic result. Clinical observation group included 10 patients. It was found that the new technique of suturing the surgical incision, in comparison with the method offered by M.B. Calobrace et al. (2014), allows to decrease the duration of suturing from 6 min 10 ± 0.06 sec down to 5 min 29 ± 0.04 sec (р < 0.01), to reduce number of stitches from 24 down to 15, to shorten postoperative stitch from 4.24 ± 0.06 cm down to 3.71 ± 0.07 cm (р < 0.01), and to shorten cicatrix length in 1 year after the operation from 4.78 ± 0.19 cm down to 4.25 ± 0.22 cm (р < 0.05). Therefore, the developed technique of suturing the surgical wound provides the location of postoperative cicatrix in the area of submammary fold which makes it less noticeable. Moreover, it allows to shorten the length of postoperative cicatrix, decrease the duration of the surgery and to secure adequate stability of implant fixation.